Export competitiveness of India's textiles and clothing sector in the United States - Misu Kim (Economies, 2019)
We analyzed India's export competitiveness in the textiles and clothing (T&C) sector in the United States. The T&C industry is traditionally important for the Indian economy due to its significant contribution to export, employment, and industrial production. However, the competition in the global T&C market intensified after the Multi-Fiber Arrangement phase-out in 2005. Therefore, it is necessary to examine the export competitiveness of India's T&C sector in the U.S., India's largest export destination and one of the world's largest consumers of T&C. In this study, we calculated the comparative advantage of India's T&C based on Revealed Comparative Advantage (RCA), Market Comparative Advantage (MCA), and Comparative Advantage by Countries (CAC). Our analysis shows that India had a comparative advantage in the T&C sector in the U.S. from 1991 to 2017, despite intensified competition in the global market.
Keywords: 330; comparative advantage; export; competitiveness; textiles and clothing industry; India; limited liberalization